Remote teaching in a school of the countryside in the state of Mato Grosso (Research, Society and Development, 2022)
This study aimed to discuss and understand the challenges faced by elementary school teachers in the use of digital resources in teaching and learning processes in remote classes in a rural school in the city of Denise-MT. The research was qualitative in nature, using a questionnaire and on-site observation. The research participants were teachers at the Joaquim Augusto da Costa Marques State School. A school in Campo do Capo located in the Municipality of Denise-MT. The results show that the challenges faced by elementary school teachers regarding the use of digital resources in teaching and learning processes in remote classes were diverse, which consisted of training for the use of digital resources, having the participation of students in synchronous classes, connection of internet, data package availability and achieving the goals set for remote classes. The most used features were the instant messaging app, Microsoft Teams platform and google meet. However, it is evident that, in the teachers' perception, the challenges imposed on them should still be means of adaptation linked to theory and practice with technologies in the teaching and learning processes. Digital technologies can be valuable resources in teaching and learning processes, even with the different difficulties between them experienced in remote learning.